Do Innovation Efficiency and Powerful Leadership Affect the Performance Effect of Technological Diversification?. (November 2019) - Huang, Yen-Chih; Lee, Cheng-Yu; Tsai, Hsin-Ju Stephie
Considering that technological diversification is rooted in distinct technological knowledge that usually comes from different business units, a firm's practices that can improve efficiency in integrating and exploiting this knowledge may be key potential moderators in this focal relationship. Based on a sample of 3, 277 firm-year observations of 435 firms in Taiwanese information and communication technology sectors during the 2004-2014 period, this study finds that technological diversification has an inverted U-shaped relationship with performance. Such relationship also can be moderated by high levels of innovation efficiency and CEO power. These findings caution against drawing universalistic normative implications for pursuing technological diversification.